1975
DOI: 10.1677/joe.0.0640141
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen, Progesterone and Corticosteroid Concentrations in Peripheral Plasma of Sows During Pregnancy, Parturition, Lactation and After Weaning

Abstract: Steroid hormone concentrations in plasma have been measured in blood samples taken from conscious sows with ear vein catheters. In late pregnancy, the plasma progesterone concentration ranged from 6 to 12 ng/ml and it decreased in all animals before the onset of parturition. Total unconjugated oestrogens increased to high values of up to about 3 ng/ml in late pregnancy and then declined after the onset of parturition. Oestrone was the predominant unconjugated oestrogen measured. Plasma corticosteroid (mainly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
2

Year Published

1976
1976
2004
2004

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(72 citation statements)
references
References 0 publications
11
59
2
Order By: Relevance
“…The peripheral plasma progesterone and oestradiol-17~ concentrations found in this study closely resemble those reported by Robertson and King (1974), Ash and Heap (1975) and F~vre et al (1975) and indicate that spontaneous parturition occurs after a change in their ratio.…”
Section: Discussionsupporting
confidence: 90%
“…The peripheral plasma progesterone and oestradiol-17~ concentrations found in this study closely resemble those reported by Robertson and King (1974), Ash and Heap (1975) and F~vre et al (1975) and indicate that spontaneous parturition occurs after a change in their ratio.…”
Section: Discussionsupporting
confidence: 90%
“…Plasma P4 decreased slowly during the days preceding parturition and more rapidly just before and during parturition as already described [24][25][26]. This decrease is due to the regression of the corpora lutea [27,28].…”
Section: Plasma Hormones Lactose and Igg Variations Around Parturitionmentioning
confidence: 52%
“…In the sow, parturition is preceded by the regression of the corpus luteum of pregnancy and the withdrawal of progesterone from the maternal circulation (Ash & Heap, 1975). The initiation of parturition was significantly delayed (P < 0-001) in all meclofenamic acid-treated sows.…”
Section: Discussionmentioning
confidence: 91%